Exploring Small Area Demand for Grocery Retailers in Tourist Areas. (April 2014) - Newing, Andy; Clarke, Graham; Clarke, Martin
This paper uses data from a major loyalty card scheme to draw insights about the characteristics of grocery expenditure by tourists. The authors explore the volume, value and composition of store-based visitor expenditure using consumer data from the loyalty card scheme. They focus on grocery spending at selected stores in Cornwall, a popular tourist destination in South West England. The loyalty card data provide a valuable source rarely available for academic investigations. The authors are able to analyse visitor spend by socio-economic and geodemographic characteristics, drawing a range of comparisons with residential demand from within the store catchment areas. They demonstrate that visitor grocery expenditure is complex and varies by store, destination and type of customer. The paper presents evidence to suggest that the current approaches used to estimate sales uplift and local-level economic impact from visitor demand are unable to account for the complexities of this form of expenditure. Based on these insights, the authors recommend that sophisticated modelling is employed to estimate the impact of visitor expenditure.